Fungi - Kratz, René Fester (--For dummies., 2026)
"Discover the fundamentals of fungi with this engaging and easy-to-follow book Fungi For Dummies gives you an in-depth view of the wide world of mycology. With this science-focused yet clear and readable book, you'll dig deep into the science of the fascinating organisms that help this planet thrive. Learn about fungi classifications and structures, their uses in and beyond medicine, their importance to environmental sustainability, and how they have shaped human cultures around the world. Go beyond the typical mushroom field guide and get a thorough introduction to the study of mycology that tracks a typical undergraduate course in the field. Grasp the basics of mycology, including how fungi grow and how they differ from plants. Discover the role fungi play in ecosystems around the world. Learn to classify the different biological structures that appear in fungi. Know the various fungal groups and their roles in nature and in human endeavors"--